Effect of acute hyperinsulinaemia with and without angiotensin II type 1 receptor blockade on resistin and adiponectin concentrations and expressions in healthy subjects - Krušinová, Eva; Klementová, Marta; Kopecký, Jan; Wohl, Pavel; Kazdová, Ludmila; Mlejnek, Petr; Pravenec, Michal; Hill, Martin; Pelikánová, Terezie (European journal of endocrinology, 2007)
OBJECTIVE: The potential insulin-sensitizing function of angiotensin II type 1 receptor blockade (ARB) with regard to selected adipokines is not fully explained so far. Our study aimed to explore the influence of acute hyperinsulinaemia and acutely induced ARB on resistin and adiponectin concentrations and expressions in healthy subjects. DESIGN AND METHODS: Plasma adipokines were measured: 1) at 0, 30 and 240 min of hyperinsulinaemic (1 mU/kg per min) euglycaemic (5 mmol/l) clamp (HEC), and 2) during HEC after acute ARB (losartan 200 mg; AT-HEC) using the same protocol, in eight healthy subjects. Needle biopsy of abdominal s.c. fat was performed at 0, 30 and 240 min of both clamps to assess the adipokines' expressions. RESULTS: Comparing the glucose disposals of HEC and AT-HEC, no difference in insulin sensitivity was found. Plasma resistin increased equally during HEC and AT-HEC (P < 0.05). The expression of resistin in s.c. fat increased during HEC (P < 0.05), while no significant changes in expression were observed during AT-HEC. Plasma levels of adiponectin did not change during both clamps. Adiponectin expression increased during HEC (P < 0.05), while it did not change during AT-HEC. CONCLUSIONS: In healthy subjects, acute hyperinsulinaemia is associated with an increase in plasma resistin independently of ARB, while plasma adiponectin is not influenced by insulin or ARB. The expressions of both resistin and adiponectin in s.c. adipose tissue are stimulated by acute hyperinsulinaemia, whereas losartan attenuates their insulin-stimulated expressions. This suggests a potential effect of losartanon adipokines' expression.
Keywords: zdraví; receptor angiotensinu typ 1; financování organizované; Hyperinsulinism; Receptor, Angiotensin, Type 1; Glucose Clamp Technique; Male; nitrobřišní tuk; resistin; adiponektin; Adiponectin; inzulin; mužské pohlaví; Insulin; Losartan; Adult; Drug Combinations; fixní kombinace léků; blokátory receptorů AT1 pro angiotensin II; Angiotensin II Type 1 Receptor Blockers; Financing, Organized; Gene Expression; hyperinzulinismus; Humans; Intra-Abdominal Fat; Resistin; glykemický clamp; exprese genu; Health; dospělí; lidé; losartan